Spectroscopic and electrochemical characterization of thio binuclear phthalocyanine complexes - Makinde, Zainab Olusola (Rhodes University, Faculty of Science, Department of Chemistry, 2017)
Expected release date-April 2019
Keywords: Uncatalogued